Pharmacotherapy for Behçet’s Disease and the Risk of Malignancy - Huang, Mao-Xin; Wang, Cai-Yun; Guo, Jin-Yan; Li, Jian-Hao; Li, Xiao-Hong; Zhang, Jiang-An; Yu, Jian-Bin (Frontiers in Pharmacology, 2021)
Abstract Background: Behcet’s disease (BD) is associated with an increased risk of cancer and few reports have been published on the relationship between drug exposure and the risk of cancer in patients with BD. Here, we explored the relationship between pharmacologic interventions for BD and the risk of cancer. Methods: we carried out a retrospective nested case-control study in a cohort of BD patients. Among 1148 BD patients, 22 cancer patients were individually 1:2 matched to 44 cancer-free controls. The following biochemical indicators were evaluated: routine analysis of blood, liver and kidney function tests, inflammatory indexes, blood gas analysis, blood electrolyte and previous pharmacologic interventions to manage BD. Systemic glucocorticoids (Glu), methotrexate (MTX), cyclosporine-A (CsA), azathioprine (AZA), cyclophosphamide (CYC), and thalidomide were considered the primary medicines used for the management of BD. Results: Among the 22 BD patients with cancers, myelodysplastic syndrome (MDS) (22.72%) were the most common types. Besides, CYC administration was significantly higher in BD patients suffering from cancers compared to the cancer-free matched control group. Further, we observed that complement 4 (C4) (OR = 0.0001,95% CI: 0.001-0.065) and hemoglobin (Hb) (OR = 0.891,95% CI: 0.795-0.998) were seen as independent protective factors for the risk of cancer in BD patients during multivariate analyses. Conclusions: Our study revealed that CYC was associated with a high risk of cancer in BD patients. Furthermore, C4 and Hb are independent protective factors for oncogenesis in BD patients. These findings may provide references and suggestions for clinicians to select drugs and early recognize high-risk patients and reduce cancer incidence in BD patients.